Metal Complexes Bearing Dianionic Trityl/Aryloxide Ligands: Rational Synthesis, Structural Diversity, and Redox Properties. Issue 17 (26th March 2020) - Huang, Zhuanying; Zhong, Tingshan; Feng, Tangbiao; Zhao, Jixing; Zhong, Hailan; Lei, Hao
Abstract : Lithium complexes containing bidentate dianionic trityl/aryloxide ligands, Li2 [ R OC](Et2 O) n ([ R OC] 2– = [κ 2 ‐ O, C ‐OC6 H2 ‐2‐C(3, 5‐R2 C6 H3 )2 ‐4, 6‐ t Bu2 ] 2– ; 2a (R = H, n = 1) and 2b (R = Me, n = 0)) were synthesized through double metalation of ortho ‐benzhydryl phenols with n BuLi. Similarly, sodium compound Na2 [ H OC](THF)2.5 (3a ) was obtained when phenol H2 [ H OC] (1a ) was treated with two equiv. of n BuLi/NaO t Bu. The lithium compounds were employed for the preparation of other metal complexes supported by [ R OC] 2– ligands, i.e. {Zn[ R OC](THF)}2 (R = H (4a ) or Me (4b )), Sn[ H OC]2 (5a ) and Cp*Ir[ Me OC] (6b, Cp* = η 5 ‐C5 Me5 ), by salt metathesis reactions with metal halides. The solid‐state structures of all metal complexes were established by X‐ray crystallography. The nuclearity of these metal complexes and the coordination fashion of the [ R OC] 2– ligands were found to be highly dependent on the identity of metal centers. Additionally, compound 2a was found to be facilely oxidized, as revealed by both electrochemical and reactivity study. Abstract : New dilithium trityl/aryloxides were synthesized and applied as effective transmetalation reagents for the preparation of [OC] complexes of Zn(II), Sn(IV), and Ir(III). Their solid‐state structures display diverse coordination modes for the alkyl/aryloxide ligands.